Public policy in the entrepreneurial society - Audretsch, David B. (Edward Elgar Pub. Ltd, 2013)
1. Do university policies make a difference? / David B. Audretsch and Erik E. Lehmann -- 2. Do knowledge conditions make a difference? : investment, finance and ownership in German industries / David B. Audretsch and Jürgen Weigand -- 3. Does the knowledge spillover theory of entrepreneurship hold for regions? / David B. Audretsch and Erik E. Lehmann -- 4. Do locational spillovers pay? : emprical evidence from German IPO data / David B. Audretsch and Erik E. Lehmann -- 5. Entrepreneurship capital and economic growth / David B. Audretsch -- 6. Location : a neglected determinant of firm growth / David B. Audretsch and Dirk Dohse -- 7. The theory of knowledge spillover entrepreneurship / David B. Audretsch and Max Keilbach -- 8. The process of creative construction : knowledge spillovers, entrepreneurship, and economic growth / Rajshree Agarwal, David Audretsch and M.B. Sarkar --
Includes bibliographical references
Keywords: Electronic books; Entrepreneurship -- Government policy; Industrial policy; Economic policy; Economic development; Unternehmer; Öffentliche Ordnung; Aufsatzsammlung